Approximate controllability of infinite dimensional linear systems in nonreflexive state spaces - Yu, Xin; Xu, Chao (Journal of control theory and applications, 2005)
This paper deals with the problem of approximate controllability of infinite dimensional linear systems in nonreflexive state spaces. A necessary and sufficient condition for approximate controllability via L^p（[0, T], U）, 1≤p〈∞ is obtained,where L^p（ [0, T], U） is the control function space.